Solid lipid nanoparticles carrying lipophilic derivatives of doxorubicin: preparation, characterization, and in vitro cytotoxicity studies. (18th May 2016) - Peira, Elena; Chirio, Daniela; Battaglia, Luigi; Barge, Alessandro; Chegaev, Konstantin; Gigliotti, Casimiro Luca; Ferrara, Benedetta; Dianzani, Chiara; Gallarate, Marina
Abstract: Doxorubicin (DOXO) lauroyl ester and amide were proposed as lipophilic derivatives and entrapped in SLNs. DOXO derivatives-loaded SLNs were spherical shaped, had 200–300 nm mean diameters and showed 80–94% w/w drug entrapment efficiencies. The effect of DOXO derivatives-loaded SLNs and free DOXO on cell growth was examined by MTT and colony-forming assays on four different tumour cell lines: a pancreatic, CFPAC-1, a lung, A549, and two ovarian, A2780 and A2780res (DOXO-resistant). The results obtained with MTT and colony-forming assay show that although DOXO displayed an inhibition of cell proliferation greater or similar to DOXO lauroyl amide-loaded SLNs on all cell types, the effect induced by DOXO lauroyl ester-loaded SLNs was higher and concentration-dependent, and it was the only one maintained at 10 −5  mM concentration. Only DOXO lauroyl ester-loaded SLNs were able to induce a 40% inhibitory effect on A2780 res cell line up to 10 −4  mM concentration.